Reader Reaction and Workplace Habits in the English Translation of French Proper Names in Canada - Mossop, Brian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis article looks at factors that might be involved in the translation of French place names and institution names into English in Canada: the anticipated reactions of readers; rules enunciated by clients, employers and style guides; the effects of workplace procedures (reduced quality control time; use of cut-and-paste translation). The possible translations of five proper names are discussed: Québec, Radio-Canada, Acadie, Commis-sion québécoise des libérations conditionnelles, Canada/canadien.